Factors impacting on reward systems: a comparative study between public and private universities in Zimbabwe - Nyanhete, Tatenda; Bhebhe, Moment (Canadian Center of Science and Education, 2021)
The aim of the research was to identify and compare the reward choices in the public and private sector and establishing the extent to which these choices were influenced by the environment. The research adopted both the quantitative and qualitative methodologies. Unstructured interviews, questionnaires and focus group discussions where used in data collection. Narrative and descriptive approaches where used in data presentation with the use of tables and matrixes to relate statistical data. The data was analysed using the thematic analysis. The major findings of the research indicated that the environment both internal and external that an organisation would be operating in did influence the reward choices. External environmental factors identified were politics, government, economic situation, sector, competition and the labour market. The internal factors were students, employees through employee associations, total costs of the organisation and management. Findings also showed that some factors of the environment affected the private and public sector differently thus resulting in different strategic choices for example the government. This confirmed the theoretical framework that reward choices were contingent upon the environment and that stakeholder concerns were taken into consideration when choosing strategies.